Personal assistants: Direct manipulation vs. mixed initiative interfaces - Armentano, Marcelo Gabriel (2006)
Interface agents are computer programmes that provide assistance to users dealing with computer-based applications. The introduction of agents to user interfaces caused the exploration of new metaphors to enhance user ability to directly manipulate interfaces. In this regard, mixed-initiative interaction refers to a flexible interaction strategy in which agents contribute with users by providing suitable information at the most appropriate time. Mixed-initiative approaches promise to dramatically enhance human-computer interaction by allowing agents to resemble human assistants. In this paper, we report a study on how the interaction metaphor can affect the user perception of agent capabilities and, in turn, the final success of agents.